Response patterns of mountain river deltas and adjacent coasts to the changes in sediment discharge: A case study of Minjiang River, China - Chengtao Wang; Feng Cai; Hongshuai Qi; Shaohua Zhao; Gen Liu; Yanyu He; Huiquan Lu; Yi Sun; Ting Zhang (Journal of Hydrology: Regional Studies)
Study region: The Minjiang River, located on the western side of the Taiwan Strait of East Asia, serves as a typical mountain river estuary system. Study focus: This research investigates the impact of reduced sediment discharge on the geomorphological changes in the Minjiang River estuary delta and its adjacent coasts. By integrating 45 years of shoreline data and nautical chart bathymetry, the study quantitatively delineates tempo-spatial change patterns and reveals the rapid response mechanisms to sediment discharge decrease. New hydrological insights for the region: The study demonstrates that the sandy shoreline near the Minjiang River estuary exhibits distinct tempo-spatial evolution patterns primarily due to decreased sediment discharge. The estuarine transition zone shows greater coastal resilience, with shoals providing essential sediment sources for development, while the shoreline south of the transition zone experiences progressively delayed erosion. The Minjiang River delta reacts swiftly to decreased sediment discharge, with a response time of significantly under ten years. Despite the temporary influence of extreme weather events such as typhoons on erosion states, continuous sediment discharge decrease remains the dominant factor. These insights highlight the heightened sensitivity and rapid adaptability of mountain rivers to environmental shifts, providing significant implications for understanding the repercussions of human activities on estuarine geomorphological alterations.